ISLAM ABANGAN DAN NASIONALISME KOMUNITAS SAMIN DI BLORA - Mukodi, Mukodi; Burhanuddin, Afid (Walisongo: Jurnal Penelitian Sosial Keagamaan, 2016)
This study aimed at exploring the starting point of Islam Abangan and nationalism among Samin community in Blora regency. This research also aimed at exposing the resistance of Samin community Blora in recent time. For this research, qualitative approach and e phenomenological method were both used to get the accurate results. Relation between Islam Abangan and nationalism among Samin community in Blora were coherently intertwined and in harmony. The harmony were manifested through the daily practices of Samin community containing the teachings of Ki Samin Surosentiko. The c onsistency  of the community in carrying out the teachings of Ki Samin Surosentiko caused them still exist to survive amid the onslaught of modernism currents. Thus, local culture, and Javanese Islam were the means to strengthen the attachment of humanity, to strengthen the humanity affinity as well as the seeds of nationalism spirit, in the regional locality, including in Blora.***Penelitian ini bertujuan untuk mengeksplorasi titik pangkal Islam Abangan, dan nasionalisme di komunitas Samin Kabupaten Blora. Selain itu, riset ini juga bertujuan untuk mengekspos daya tahan eksistensi komunitas Samin Blora yang masih hidup hingga kini. Agar menemukan hasil yang akurat riset ini menggunakan pendekatan kualitatif dengan metode fenomenologi. Relasi antara Islam Abangan, dan nasionalisme di kalangan komunitas Samin Brola terjalin padu, dan harmoni. Keharmonian keduanya terejawantahkan melalui praktik-praktik keseharian mereka yang merupakan nilai ajaran Ki Samin Surosentiko. Konsistensi komunitas Samin dalam menjalankan ajaran Ki Samin mengakibatkan mereka tetap eksis bertahan di tengah gempuran arus modernisme. Dengan demikian, kebudayaan lokal, dan Islam (Jawa) Abangan menjadi sarana untuk memperkokoh kelekatan kemanusiaan, sekaligus penyemai jiwa nasionalisme di bilik-bilik lokalitas kedaerahan, tak terkecuali di Blora.